Sobreviventes da COVID-19 pós-alta hospitalar: necessidades e acesso à reabilitação - Silva, Vitória Polliany De Oliveira (2023)
Introduction: Due to the complex pathophysiological process of Covid-19 and the need for prolonged hospitalization in severe cases, survivors of this infection may persist long-term with different types of complications and degrees of functional impairment. In such cases, post-hospital discharge rehabilitation becomes a necessity. However, it is known that in Brazil, health rehabilitation actions are limited and do not yet guarantee access to all people who need it. Objective: To analyze the needs and access to post-hospital discharge rehabilitation among Covid-19 survivors in the municipality of João Pessoa-PB. Method: This is a descriptive, cross-sectional study with a qualitative and quantitative approach, developed in a public hospital for the treatment of Covid-19. The research sample consisted of individuals who were discharged after hospitalization for Covid-19 between 2020 and 2021. The study was developed in four phases: 1) Survey at the SAME; 2) Analysis of medical records; 3) Application of forms via telephone call; and 4) Structured interviews via the Google Meet platform. Descriptive and inferential statistics, as well as the WoE binary classification model and logistic regression, were used to analyze the quantitative data. The qualitative data were treated through content analysis. Results: About 88.9% of the patients reported complaints after hospital discharge. The main complaints identified were dyspnea (67.9%), anxiety (40.7%), and memory loss (35.8%). However, only 22 patients had access to rehabilitation, with a prevalence in the private network (63.6%). In the WoE model, dyspnea, income, myalgia, and sex variables were classified as very strong in explaining the outcome. Furthermore, the odds ratio results showed that patients with dyspnea complaints have 28.163 times more chance of accessing rehabilitation after discharge. In addition, the results of the interviews allowed us to identify that the social support network of the subjects can influence the search process for rehabilitation. Final considerations: The results of this research highlight the need for the development of strategies that ensure adequate access to rehabilitation for individuals with long Covid in the public health network, as well as may support decision-making processes by managers.